Movimento estudantil brasileiro: Práticas militantes na ótica dos Novos Movimentos Sociais - Marcos Ribeiro Mesquita (Revista Crítica de Ciências Sociais, 2003)
The author analyzes the relationships among the various organized groups that comprise the student movement, ranging from the most institutionalized to those that prefer non-institutionalized ways to take part in politics. The plurality of student expressions, their new forms, new methods, and new issues support the hypothesis that there really is such a new sociability, despite the strong traditional character that the institutionalized student movements still hold.